Marketability of pizza business in Iloilo City - Castor, Ann Marie; Doce, Irese; Roa, Honey Faith; Serue, Katheryn; Suresca, Merly; Yeh, Katheryn Joanne (2007.)
The research study entitled, " Marketability of pizza business in Iloilo city" was undertaken from June 18, 2007 to September 16, 2007. Its objectives are to identify and describe the factors that influence the putting up of a business, to identify and describe the problems encountered by the management of pizza parlors in Iloilo City, and to recommend better marketing strategies to increase the marketability of pizza. The 5 P's of Marketing and the consumer Decision Making ProcessModel developed and popularized by E. Jerome McCarthy and Philip Kotler, respectively, were used as basis for the identification of the factors which affect the marketability of pizza restaurants in the city. The study has two types of participants, namely, the owners, managers, and employees of pizza parlors in Iloilo City for the seller perspective, and the 209 University of the Philippines Visayas-College of Management (UPV_CM) students for the pizza consumer perspective. The above-mentioned owners, managers, and employees were interviewed and the students were surveyed to gather data. The students' sample size (209) was identified through the use of Slovin's formula. Research results show that pizza business is popular in Iloilo City especially to UPV-CM students. These results indicate that pizza is profitable in Iloilo City and that the use of strategic marketing tools is a factor that contributes to this. Based on trends observed, pizza managers and owners must have strategic marketing techniques to expand and retain market share. Further studies about the marketability f pizza business in the whole Panay and Bacolod, and whether pizza parlors can stand alone having pizza products as the only offering, are also recommended.
Research Paper (Mgt 199-Management Research). -- [Iloilo City : University of the Philippines Visayas-College of Management], October 11, 2007.